2012
DOI: 10.1161/hypertensionaha.112.198630
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Continuous-Flow Left Ventricular Assist Devices Provide Insight in Human Baroreflex Physiology

Abstract: Abstract-The superior clinical outcome of new continuous-flow left ventricular assist devices (LVADs) challenges the physiological dogma that cardiovascular autonomic homeostasis requires pulsatile blood flow and pressure. We tested the hypothesis that continuous-flow LVADs impair baroreflex control of sympathetic nerve traffic, thus further exacerbating sympathetic excitation. We included 9 male heart failure patients (26 -61 years; 18.9 -28.3 kg/m 2 ) implanted with a continuous-flow LVAD. We recorded ECG, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Notably, Tank et al 19 performed a similar analysis of patients with centrifugal-flow (Heartware) ventricular assist devices and found that pulsatility was not significantly changed by increasing pump speed and that there was a very slight reduction in MSNA (by 3 bursts per minute) as pump speed was raised from baseline to 3200 RPM. Baseline MSNA in their subjects was comparable to our cohort; however, their healthy control subjects had MSNA levels that were much higher than healthy control subjects that we have evaluated previously and were similar to MSNA levels in their LVAD patients.…”
Section: Baroreceptor Physiology During Nonpulsatile and Pulsatile Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Tank et al 19 performed a similar analysis of patients with centrifugal-flow (Heartware) ventricular assist devices and found that pulsatility was not significantly changed by increasing pump speed and that there was a very slight reduction in MSNA (by 3 bursts per minute) as pump speed was raised from baseline to 3200 RPM. Baseline MSNA in their subjects was comparable to our cohort; however, their healthy control subjects had MSNA levels that were much higher than healthy control subjects that we have evaluated previously and were similar to MSNA levels in their LVAD patients.…”
Section: Baroreceptor Physiology During Nonpulsatile and Pulsatile Flowmentioning
confidence: 99%
“…Indeed, it may be that centrifugal-flow devices are less able to introduce pulsatile flow through modulations in pump speed. 19 Second, all of the patients were on β-blockers, which were held on the morning of the study. This eliminated the acute effects of β-blockade on MSNA, but we cannot rule out the possibility that chronic effects of the drug were still present.…”
Section: Limitationsmentioning
confidence: 99%
“…Those living with LVADs constitute a small population but one for whom there has been an enormous investment in resources and personnel to ensure a good and enduring outcome with a high quality of life. The value of MSNA, as revealed by the present literature, [4][5][6] is that it could well be applied in future investigations to define the optimal degree of pulse and diastolic pressure for such individuals. …”
Section: Floras Et Al Lvad Pulse Pressure and Msna 2295mentioning
confidence: 76%
“…Increasing pump speed lowered pulse pressure to 5 mm Hg, yet MSNA fell. 6 A clinical stimulus to the present study was the investigators' contention that nonpulsatile flow induces a "hyperadrenergic environment." However, the average MSNA burst…”
Section: Article See P 2316mentioning
confidence: 99%
See 1 more Smart Citation